Modelling knowledge in embedded product design - electronic design issues / Mohd Nazri Mustafa - Mustafa, Mohd Nazri (2012)
Corporate memory, known as corporate knowledge is an organizational memory. It is made up of the aggregate intellectual assets of organizations. Corporate knowledge is a combination of both explicit and tacit knowledge. Type of corporate knowledge is depends on the domain and nature of the organizations. In organizations that doing research and developments, electronics product designs knowledge regards as one of corporate knowledge. Knowledge sharing grows corporate memory by constantly adding new knowledge to the organizations. However, retrieval of knowledge becomes a complex process when knowledge was recorded manually with uncertain storing location. Thus, it is important to have a system that can capture, store and retrieve knowledge. In order to develop such system, knowledge need to be structure and model. Model is used to capture the essentials features of real systems by breaking them down into more manageable parts that are easy to understand and to manipulate. Models are very much associated with the domain they represent. Even though in tangible form, most of the knowledge was unstructured. In MIMOS, the corporate knowledge which is in tacit form is very much embedded in the employee skills. Therefore, the product design knowledge is more on tacit rather than explicit. In the process of product design, the tacit knowledge is actively transforms to explicit knowledge in form of documents such as issue list and root-cause analysis. Hence, this project will emphasize on modeling product design knowledge based on available documents.